Traditional Knowledge Aids Description When Resolving the Taxonomic Status of Unsettled Species Using Classical and Molecular Taxonomy: The Case of the Shallow-Water Octopus Callistoctopus furvus (Gould, 1852) From the Western Atlantic Ocean - Jesus, Manuella Dultra; Sales, João Bráullio de Luna; Martins, Rodrigo Silvestre; Ready, Jonathan Stuart; Costa, Tarcisio Augusto S.; Ablett, Jonathan D.; Schiavetti, Alexandre (Frontiers in Marine Science, 2021)
Shallow-water marine invertebrate fauna is diverse in tropical latitudes but generally poorly known. This is in part due the remoteness of many of these regions, and a lack of locally trained taxonomists. In such cases, the ethnoknowledge (i.e., information acquired from the sociocultural references of a given social group) of traditional human populations may be a valuable tool to elucidate gaps in the occurrence of some taxa. In this study, we used a combined approach of ethnoknowledge, classic taxonomy and molecular techniques to describe and diagnose an unsettled species of shallow-water octopus of the genus Callistoctopus. A neotype for the Brazilian eastern octopus Callistoctopus furvus (Gould, 1852) is described along with some ecological notes. Octopuses were collected between April and May 2018 during field trips guided by artisanal octopus fishers of Bahia State (Brazil). A linear discriminant analysis showed that the morphology of C. furvus overlapped poorly with Callistoctopus sp. from the Caribbean and Macaronesia (Madeira Archipelago) as well as with Callistoctopus macropus stricto sensu from Mediterranean Sea. Analysis of mitochondrial large ribosomal subunit (rrnL, also known as 16S) gene and cytochrome C oxidase I (COI) showed that C. furvus differs genetically from European C. macropus and the other species in the genus. In general, C. furvus differs from other Atlantic/Mediterranean Callistoctopus species in having a slender body shape and longer mantle lengths. As in other species of the genus, C. furvus is nocturnal and inhabits sandy bottoms, seagrass beds and/or low-profile reefs. Interestingly, C. furvus burrows itself into the sand as a defense mechanism. In conclusion, we showed the support of ethnoknowledge for integrative biodiversity assessments in poorly surveyed remote areas in the western tropical Atlantic.